Policy Implications of "Second-Generation" Crisis Models - Marion, Nancy (IMF Working Papers; Working Paper, 1997)
After the speculative attacks on government-controlled exchange rates in Europe and in Mexico, economists began to develop models of currency crises with multiple solutions. In these models, a currency crisis occurs when the economy suddenly jumps from one solution to another. This paper examines one of the new models, finding that raising the cost of devaluation may make a crisis more likely. Consequently, slow convergence to a monetary union, which increases the cost to the government of reneging on an exchange rate peg, may be counterproductive. This conclusion is exactly the opposite of that obtained from earlier models.